2020
DOI: 10.3389/fmicb.2020.00496
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Amoxicillin-Induced Perturbation of the Gut Microbiota Promotes Acute Intestinal Immune Regulation in Brown Norway Rats

Abstract: The intestinal gut microbiota is essential for maintaining host health. Concerns have been raised about the possible connection between antibiotic use, causing microbiota disturbances, and the increase in allergic and autoimmune diseases observed during the last decades. To elucidate the putative connection between antibiotic use and immune regulation, we have assessed the effects of the antibiotic amoxicillin on immune regulation, protein uptake, and bacterial community structure in a Brown Norway rat model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 80 publications
(95 reference statements)
3
40
0
2
Order By: Relevance
“…It has been reported that the impact of antibiotics on the gut microbiome can be attributed to its antimicrobial spectrum and the antimicrobial activity in the colon depending on concentrations [ 46 , 47 ]. Previous studies examined the effect of several types of antibiotics on the perturbation of gut microbiota, which may lead to an alteration in colonic mucosal homeostasis and microbial metabolites [ 18 , 27 , 48 , 49 ]. Høverstad et al reported that considerably changed SCFA profiles were observed according to the administration of ampicillin (500 mg four times daily) in the human clinical trial [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the impact of antibiotics on the gut microbiome can be attributed to its antimicrobial spectrum and the antimicrobial activity in the colon depending on concentrations [ 46 , 47 ]. Previous studies examined the effect of several types of antibiotics on the perturbation of gut microbiota, which may lead to an alteration in colonic mucosal homeostasis and microbial metabolites [ 18 , 27 , 48 , 49 ]. Høverstad et al reported that considerably changed SCFA profiles were observed according to the administration of ampicillin (500 mg four times daily) in the human clinical trial [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The administration of antibiotics has been widely applied in the treatment and prevention of infectious diseases [ 26 ]. However, fewer studies have been conducted to evaluate the effect of antibiotics on the VFA profiles of the gut microbiota [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contradictory findings exist in the literature with humans, laboratory animals and in vitro studies reporting high interindividual effects [68], no effects [69,70], only shortterm effects [62,65], or both short-and long-term effects on microbial composition [60,71,72] after administration of amoxicillin with or without clavulanic acid. In a study in rats, a 7-day course of amoxicillin during the weaning period caused transient alterations in microbial composition that resolved by 20 days after its discontinuation [61].…”
Section: Discussionmentioning
confidence: 99%
“…Increased abundance of different species were observed by the end of treatment. Antibiotics, including doxycycline and amoxicillin most commonly either decrease [58][59][60][61][62], or do not have any effect on species richness [63]. Only few studies have reported an increase in species richness indices [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the intestinal microbiota plays an important role in modulating the immune system against viruses (12)(13)(14)(15). The regulatory effects of the intestinal microbiota on viral infection are closely intertwined with local and systemic immune responses and contribute to both congenital and adaptive immune responses (16,17).…”
Section: The Regulatory Effects Of Intestinal Microbiota On Immunitymentioning
confidence: 99%